Efeitos eletrônicos, elásticos e estruturais em sistemas semicondutores nanoscópicos - Cesar, Daniel Ferreira (Universidade Federal de São Carlos, 2012)
The present work aims the study of electronic, elastic and structural properties of a whole class of nanoscopic semiconductors systems, which include quasi-two-dimensional, one-dimensional and zero-dimensional confined systems. Within two-dimensional systems, the effects caused by strain and temperature on the electronic structure of AlGaAs=GaAs multiple quantum wells oriented along [001] and [113] crystallographic directions were studied. The energy difference between light- and heavy-hole states as a function of temperature, for both crystallographic directions, was obtained from photoluminescence spectra. Using k _ p calculations, it was possible to phenomenologically explain experimental data and to show that electronic structure of quantum wells grown along [113] direction presents higher sensitivity to temperature variation. A second task in quasi-two-dimensional systems was the study of the magnetic response of neutral excitons in AlGaAs=GaAs simple quantum wells grown along [110] crystallographic direction. The Zeeman splitting and the degree of circular polarization (DCP) for the sample was extracted from circularly polarized photoluminescence spectra. Using k _ p calculations, it was possible to show that the valence band presents a high hybridization of spin states in this kind of system. To simulate the relative occupation of hybridized states, a dynamic model for spin relaxation combined with electronic structure calculations was performed. Based on theoretical results, the experimental data of the Zeeman splitting and DCP were satisfactorily and phenomenologically explained. As the last task in quasi-two-dimensional systems, the effect of in-plane magnetic field in a AlGaAs=GaAs double quantum well system was studied. As the main result, the envelope functions required for an efficient k _ p calculation in this kind of system was constructed. Concerning one-dimensional confined systems, structural properties of a twin-plane superlattice in InP nanowires were studied. The system was simulated along [111] crystallographic direction by molecular dynamics. The latter provided, besides nanowire atomic structure, stress tensor elements and elastic constants at T = 0 K. Giving the molecular dynamics results, it was possible to theoretically calculate strain tensor components and the potential profiles at the valence and conduction energy bands. The calculations showed how the strain potential profiles modulate the electronic band structure of the nanowire, generating a one-dimensional superlattice. Finally, within zero-dimensional confined systems, dynamic effects detected in the time-resolved emission from InAs quantum dots ensembles were studied. To explain the experimental behavior of the time decay as a function of quantum dots emission energy, the electron-phonon interaction, considering Fröhlich Hamiltonian model, and a carrier dynamics, that takes in account nonlinear effects such as carrier imbalance, were included in theoretically calculations. The theoretical results show that, when the system behaves like an ensemble, collective effects predominate, and different relaxation processes stand out in the system, distinguishing it from that one of isolated quantum dots. By means of theoretical calculations it was possible to satisfactorily explain the experimental data.
Keywords: Física da matéria condensada; Nanoestrutura - propriedades ópticas; Semicondutores III-V; Estrutura eletrônica; Método k.p; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA